Model and Technology for Prioritizing the Implementation of end-to-end Business Process Components of the Green Economy - Chalyi, S.; Levykin, I.; Guryev, I. (My University, 2020)
Model and Technology for Prioritizing the Implementation of end-to-end Business Process Components of the Green Economy
Keywords: Green Economy